Undergraduate nursing students’ knowledge and attitudes towards Primary Health Care - Nafa Odeh; Rabia S. Allari (PLOS Global Public Health, 2026)
This study aimed to assess undergraduate nursing students’ knowledge and attitudes toward Primary Health Care in Jordan. This study adopted a descriptive cross-sectional design, involving 157 nursing students from two private and two public universities in the central region of Jordan. It utilized an Arabic version of a self-administered online Primary Health Care Questionnaire. The findings indicated that the majority of students exhibited high knowledge (77%) and positive attitudes (97%); however, there was a significant difference between students’ knowledge, attitudes, and their socio-demographic factors. Moreover, the results revealed that demographic factors affect primary healthcare attitudes and knowledge, indicating that students’ perspectives concerning PHC can be influenced by demographic factors, including gender (B = 0.173), academic performance (B = 0.044), and intent to leave nursing in the future (B = 0.122) at a significance level (